Effect of oat intake on glycaemic control and insulin sensitivity: a meta-analysis of randomised controlled trials. Issue 3 (14th August 2014) - Bao, Lei; Cai, Xiaxia; Xu, Meihong; Li, Yong
<x content-type="archive" xml:space="preserve">Abstract</x> The present meta-analysis of randomised controlled trials (RCT) aimed to investigate the effect of oat intake on glycaemic control and insulin sensitivity. A literature search was carried out in PubMed, ScienceDirect Online and The Cochrane Library (up to October 2013) for RCT that assessed the effect of oat intake on glucose control and insulin sensitivity. A total of fifteen articles with 673 subjects met the inclusion criteria. A random-effects model was used when the overall pooled studies exhibited significant heterogeneity. Otherwise, a fixed-effects model was used. Compared with controls, oat intake significantly reduced the concentrations of fasting insulin by − 6·29 (95 % CI − 12·32, − 0·27) pmol/l (P= 0·04) and the values of glucose AUC (GAUC; 0–120 min) by − 30·23 (95 % CI − 43·65, − 16·81) min × mmol/l (P< 0·0001). There was a slight decrease in fasting glucose concentrations, glycated Hb concentrations and homeostatic model assessment-insulin resistance values in subjects who consumed oats, but the difference was not significant. In conclusion, oat intake significantly lowers fasting insulin concentrations and GAUC values. To further investigate the effect of oat intake on fasting glucose concentrations, additional long-term and high-quality RCT with a parallel design are required.